2012
DOI: 10.2355/isijinternational.52.2273
|View full text |Cite
|
Sign up to set email alerts
|

Iron Aluminide Coatings by Electrodeposition of Aluminum from an Organic Bath and Subsequent Annealing

Abstract: Oxidation-resistant Fe-Al alloy coatings were formed on Fe substrate by a process using electrodeposition of Al and annealing. Electrodeposition in a dimethylsulfone-aluminum chloride bath containing an additive at 110°C yielded a dense Al layer adherent to the Fe substrate. Annealing of the Fe substrate with the electrodeposited Al layer generated an Fe2Al5 layer on the surface at 700°C and 800°C, and an FeAl layer at 900°C through interdiffusion. Oxidation tests at 600°C and 800°C confirmed that the FeAl lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Compared to etheric and aromatic baths, sulfonic baths have lower flammability and toxicity, making them safer and easier to handle. While the electrodeposition of smooth, dense Al coatings from dimethylsulfone (DMSO 2 )/AlCl 3 baths has been previously reported [2,5,[19][20][21][22], it was performed at a relatively high temperature, typically 110 • C-130 • C (because the melting point of DMSO 2 is 109 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to etheric and aromatic baths, sulfonic baths have lower flammability and toxicity, making them safer and easier to handle. While the electrodeposition of smooth, dense Al coatings from dimethylsulfone (DMSO 2 )/AlCl 3 baths has been previously reported [2,5,[19][20][21][22], it was performed at a relatively high temperature, typically 110 • C-130 • C (because the melting point of DMSO 2 is 109 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relationship between the concentration of AlCl 3 and the ionic species observed in the bath and on the electrodeposition of Al was investigated by NMR spectroscopy. 27 Al NMR spectroscopy was used, as this technique allows the environment of Al atoms to be unambiguously determined in most cases. As previously reported, octahedral Al is found at chemical shifts of around 0 ppm in the 27 Al NMR spectra, while tetrahedral Al is found around 100 ppm [35][36][37].…”
Section: Nmr Measurements Using Various Alcl 3 / Dmso 2 Mixturementioning
confidence: 99%
“…However, Al-coating has been achieved using non-aqueous media such as organic solvents, molten salts, and ionic liquids [11][12][13][14][15][16][17][18][19]. Of these options, the organic solvent dimethylsulfone (DMSO 2 , (CH 3 ) 2 SO 2 ) is advantageous, as it is inexpensive compared to ionic liquids and more stable than ethers and aromatic hydrocarbons [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be used at a lower temperature (110°C) than the molten salts (N140°C). It has been demonstrated that dense, uniform Al coatings with high corrosion resistance can be electrodeposited in a DMSO 2 -AlCl 3 bath [27][28][29][30][31][32][33][34][35]. The electrodeposition can be performed at higher rates (40-80 mA cm −2 ) in this bath than in ionic liquids without dendritic growth.…”
Section: Introductionmentioning
confidence: 97%